The calcium chloride-induced rodent model of abdominal aortic aneurysm - Wang, Yutang; Krishna, Smriti; Golledge, Jonathan (Atherosclerosis, 2013)
Abdominal aortic aneurysm (AAA) affects ∼5% men aged over 65 years and is an important cause of death in this population. Research into AAA pathogenesis has been fuelled by the need to identify new diagnostic biomarkers and therapeutic targets for this disease. One animal model of AAA involves peri-vascular application of calcium chloride (CaCl2) onto the infra-renal aorta of mice and rats to induce extracellular matrix remodelling. Twenty-three studies assessing CaCl2-induced AAA and six studies assessing AAA induced by a modified CaCl2 method were identified. In the current report the preparation and pathological features of this AAA model are discussed. We also compared this animal model to human AAA. CaCl2-induced AAA shows the following pathological characteristics typically found in human AAA: calcification, inflammatory cell infiltration, oxidative stress, neovascularisation, elastin degradation and vascular smooth muscle cell apoptosis. A number of mechanisms involved in CaCl2-induced AAA have been identified which may be relevant to the pathogenesis of human AAA. Key molecules include c-Jun N-terminal kinase, peroxisome proliferator-activated receptor-γ, chemokine (C–C motif) receptor 2, group x secretory phospholipase A2 and plasminogen. CaCl2-induced AAA does not display aortic thrombus, atherosclerosis and rupture which are classical features of human AAA. Advantages of the CaCl2-induced AAA technique include (1) it can be applied to wild type mice making assessment of transgenic rodent models more straight forward and rapid; and (2) CaCl2-induced AAAs are usually developed in the infra-renal abdominal aorta, which is the most common location of human AAA. Currently findings obtained from the CaCl2-induced AAA model or other animal models of AAA have not been translated into the human situation. It is hoped that this deficiency will be corrected over the next decade with a number of clinical trials currently examining novel treatment options for AAA patients.